EVALUATION OF ESSENTIAL OILS AS A GLAZING MATERIAL FOR FROZEN RAINBOW TROUT (ONCORHYNCHUS MYKISS) FILLET - Coban, Ozlem Emir (Wiley-Blackwell, 2013)
In this study, sage, thyme and clove oils were evaluated as a glazing material for rainbow trout (Oncorhynchus mykiss) frozen. One percent sage, thyme and clove oil solutions were used for glazing. Water-glazed (WG) and nonglazed (NG) rainbow trout fillets were used as controls. Fish fillets were glazed and were stored in a freezer at -18C for 6 months. Samples were analyzed at 1, 2, 3, 4, 5 and 6 months for moisture content, total volatile basic nitrogen, thiobarbituric acid, peroxide value, free fatty acids and sensorial quality. It was determined that glazed samples had higher moisture content compared to NG trout fillet after 6 months storage. Essential oils were effective in controlling lipid oxidation in rainbow trout fillet (P<0.05). PRACTICAL APPLICATIONSFreezing is one of the most employed methods used for preserving fresh fish and other seafood products. However, frozen storage does not completely inhibit chemical reactions (e.g., lipid oxidation) that lead to quality deterioration of fish and fish product. The antioxidant property of some essential oils may make it ideal for use as a glazing solution for suppressing lipid oxidation in rainbow trout fillet during frozen storage.
Keywords: Perch Lates-Niloticus; Quality Deterioration; Antioxidant Activity; Oxidative Stability; Rosemary Extract; Chemical-Changes; Tea Extracts; Shelf-Life; Storage; Fish